PERAN IT MENGGUNAKAN IMPORTANCE-PERFORMANCE ANALYSIS PADA MASYARAKAT KRISIS EKONOMI YANG TERDAMPAK PANDEMI COVID-19 DI RAWALUMBU BEKASI - Yunus Fadhillah (Jupiter: Journal of Computer & Information Technology, 2021)
The COVID-19 pandemic which began to spread in Indonesia at the end of 2019 until now has had an impact on the community, especially Bekasi Rawalumbu, mostly affected economically and socially. Overcoming the economic impact of the epidemic and social restrictions from the government, the community is making efforts to overcome the economic crisis by using information technology on the market. To find out the role of information technology in overcoming the economic impact on society, the method of gap analysis, importance-performance analysis, field observations, and surveys are validated and the reliability of the affected community is used. The role of this technology can be enhanced and empowered in overcoming the economic crisis caused by the epidemic.